High efficient dye sensitized solar cells using phthaloylchitosan based gel polymer electrolytes. (10th August 2017) - Buraidah, M.H.; Shah, Shahan; Teo, L.P.; Chowdhury, Faisal I.; Careem, M.A.; Albinsson, I.; Mellander, B.-E.; Arof, A.K.
Abstract: High efficiency of 9.61% has been produced for dye sensitized solar cell using a phthaloylchitosan based gel polymer electrolyte. The gel polymer electrolytes have been optimized by varying the amount of tetrapropylammonium iodide (TPAI) and 1-butyl-3-methylimidazolium iodide (BMII) ionic liquid (IL). The highest ionic conductivity of gel polymer electrolyte containing 8 wt.% IL was obtained with the value of 13.5 mS cm −1 . The temperature dependence ionic conductivity follows Arrhenius rule. The highest conducting electrolyte also exhibits the highest diffusion coefficient of triiodide ion which is 3.9 × 10 −7 cm −2 s −1 . The optimized gel polymer electrolyte exhibits the highest short circuit current density of 19.68 mA cm −2 .